PROTOCOL: The effects of small class sizes on students' academic achievement, socioemotional development, and well‐being in special education. Issue 2 (16th May 2021) - Bondebjerg, Anja; Dalgaard, Nina T.; Filges, Trine; Thomsen, Morten K.; Viinholt, Bjørn C. A.
Abstract: This is the protocol for a Campbell review. The objective of this systematic review is to uncover and synthesise data from studies to assess the impact of small class sizes on the academic achievement, socioemotional development, and well‐being of students with special educational needs. Where possible, we will also investigate the extent to which the effects differ among subgroups of students. Furthermore, we will perform a qualitative exploration of the experiences of children, teachers, and parents with special education class sizes.